2020
DOI: 10.1177/1076029620940050
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9 (TLR9) Gene C/T (rs352140) Polymorphisms in Adult Primary Immune Thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease characterized by low platelet count and increased bleeding risk. The initial event(s) leading to antiplatelet autoimmunity remains unclear. Toll-like receptors (TLRs) are the most well-characterized pattern recognition receptors and are a transmembrane protein coded by the Toll genes family. In addition to their protective role in immunity, it is also becoming clear that TLRs exhibit homeostatic roles. Toll-like receptors play potential roles in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…There was a statistically significant difference between studied patients’ platelet count as regards to WHO bleeding scale. This is in agreement with Di Micco and Monreal, 22 Hassan and colleagues 23 who confirmed that patients with a very low platelet count had a higher rate of major bleeding, 1.2% of these patients had <80 000 platelet/µL and revealed that these patients had increased risk for major bleeding and fatal bleeding than those with normal platelet count.…”
Section: Methodssupporting
confidence: 90%
“…There was a statistically significant difference between studied patients’ platelet count as regards to WHO bleeding scale. This is in agreement with Di Micco and Monreal, 22 Hassan and colleagues 23 who confirmed that patients with a very low platelet count had a higher rate of major bleeding, 1.2% of these patients had <80 000 platelet/µL and revealed that these patients had increased risk for major bleeding and fatal bleeding than those with normal platelet count.…”
Section: Methodssupporting
confidence: 90%
“…By contrast, no association was encountered between TLR9 rs5743836 (or -1237T/C) promoter polymorphisms and the risk of gastric cancer[ 38 ]. The role of TLR9 rs352140 polymorphism was assessed in patients with different conditions such as renal transplantation[ 39 ], systemic lupus erythematous[ 40 ], bacterial meningitis[ 41 ], primary immune thrombocytopenia[ 42 ], cervicitis[ 43 ], cervical cancer[ 44 ], or placental inflammation[ 45 ]. In terms of gastropathy and TLR9 rs352140 SNP, the data are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the TLR9 gene showed one variant c.1635G>A (p.P545P, rs352140) (Supporting information Table 3) with a genotype distribution in this study group of 25% heterozygotes GA, 25% homozygotes AA and 50% homozygotes GG. The rs352140 polymorphism was already notified in several disorders, such as primary immune thrombocytopenia [28], systemic lupus erythematosus [29], vasculitis [30] and HCV [31], highlighting a primary role of this polymorphism in the dysregulation of immune response in susceptible individuals. Therefore, in our study, the identification of specific SNPs seems not to correlate with an imbalance between TLR9 protein and transcript level in IMNM, but they are probably involved in the modulation of immune response promoting necrotizing myopathies.…”
Section: Discussionmentioning
confidence: 99%